The Effects of Anlotinib Combined with Chemotherapy following Progression on Cyclin-Dependent Kinase 4/6 Inhibitor in Hormone Receptor-Positive Metastatic Breast Cancer - Ting Xu; Weili Xiong; Lili Zhang; Yuan Yuan (The Breast Journal)
Purpose. Endocrine therapy combined with cyclin-dependent kinase (CDK) 4/6 inhibitors (CDK4/6i) is the preferred treatment for hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2–) metastatic breast cancer (MBC). However, there are currently no recommendations for therapeutic strategies after progression on CDK4/6i-based treatment. This study aimed to examine the efficacy and safety of anlotinib plus chemotherapy in HR+/HER2– MBC after progression on CDK4/6 inhibitors. Methods. We collected data from 32 patients with HR+/HER2– MBC treated with anlotinib plus chemotherapy after progressing on CDK4/6i at Jiangsu Cancer Hospital from March 2020 to October 2023. The median follow-up was 9.1 months (range, 2.0–19.7 months) as of the data cutoff date in October 2023. The primary endpoint was median progression-free survival (PFS); secondary endpoints included objective response rate (ORR), disease control rate (DCR), and adverse events. Results. The median PFS (mPFS) of all patients was 7.6 months (95% confidence interval (CI), 5.75–9.45). There was no significant difference in mPFS between patients who responded to prior CDK4/6i treatment and those who did not (8.3 months vs. 6.8 months, p=0.580). Besides, the ORR was 34.4% and DCR was 93.8%. The most frequently observed adverse events were anemia (50.0%), neutropenia (40.6%), thrombocytopenia (34.4%), and epistaxis (34.4%). Dose interruption or reductions due to adverse events occurred in 2 (6.3%) and 5 (15.6%) patients, respectively. Conclusions. The study preliminarily demonstrates that anlotinib combined with chemotherapy may be an optional recommendation for patients with HR+/HER2– metastatic breast cancer who have progressed after CDK4/6i.